Resource Malallocation within Firms - Enke, Stephen (Quarterly Journal of Economics, 1949)
Journal Article Resource Malallocation within Firms Get access Stephen Enke Stephen Enke University of California, Los Angeles Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 63, Issue 4, November 1949, Pages 572–576, https://doi.org/10.2307/1882141 Published: 01 November 1949